IDENTIFICATION OF DYNAMIC STRAIN MONITORING LOCATIONS FOR THE MAIN BEARINGS OF AN INTEGRAL ENGINE-COMPRESSOR USING FINITE ELEMENT MODELING - Tomsick, Alexander Michael, author; Olsen, Daniel, advisor; Stansloski, Mitchell, advisor; Heyliger, Paul, committee member (Colorado State University. Libraries, 2026)
The aging fleet of integral engine-compressors remains the backbone of the North American gas transmission industry. Replacement of these integral engine-compressors is currently not cost-effective due to the extreme operational availability requirements. Given this, it is more important now to utilize a preventative maintenance program that uses condition-based data, which measures performance and health metrics to guide maintenance actions. The health of most components of an integral engine-compressor can be understood through the collection of routine performance analysis data. However, the typical technologies utilized during these performance analyses do not adequately offer insight into the condition of the main bearings. This research aims to evaluate the measurement of dynamic strain on the main bearing saddles of a large integral engine-compressor to measure their condition during operation. To determine the most effective locations for measuring dynamic strain on the main bearings of a reciprocating machine, a time-dependent finite element model of the rotating assembly of an Ingersoll Rand KVSR 412 was created in ANSYS Mechanical. The loads on the main bearings, which were output from this model, included the effect of both the inertial loads caused by the rotating crankshaft and the reciprocating components, and the gas loads caused by changes in power and compressor cylinder pressures, which varied with time. To ensure accuracy, gas loads applied to the model were calculated using cylinder pressures, which were measured from a KVSR 412 operating at a natural gas compressor station located in Northeastern Utah. The results of the finite element modeling showed that the most effective location for measuring dynamic strain varies between main bearings. This location is dependent on the distance of the nearest compressor cylinder and the number of power cylinders that neighbor each main bearing. In addition to the finite element modeling, dynamic strain sensors were installed on the main bearings of the same KVSR 412 from which the cylinder pressure data was measured. These sensors were installed for the collection of main bearing strain data during the operation of the integral engine-compressor. This data collection is planned as part of the future work of this research.